2021
DOI: 10.3389/fimmu.2021.704172
|View full text |Cite
|
Sign up to set email alerts
|

Lung Allograft Epithelium DNA Methylation Age Is Associated With Graft Chronologic Age and Primary Graft Dysfunction

Abstract: Advanced donor age is a risk factor for poor survival following lung transplantation. However, recent work identifying epigenetic determinants of aging has shown that biologic age may not always reflect chronologic age and that stressors can accelerate biologic aging. We hypothesized that lung allografts that experienced primary graft dysfunction (PGD), characterized by poor oxygenation in the first three post-transplant days, would have increased biologic age. We cultured airway epithelial cells isolated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Emerging research shows that lung transplant-related injury may lead to accelerated aging in the graft and that senescence can be transmitted from transplanted cells. 13,14 Finally, it is possible that some latent driver of both frailty and CLAD could explain our findings. If it turns out that 1 of the latter 2 broad potential relationships is true, it would suggest that frailty may be an early "biomarker" of CLAD risk rather than lying on the causal pathway.…”
Section: Discussionmentioning
confidence: 85%
“…Emerging research shows that lung transplant-related injury may lead to accelerated aging in the graft and that senescence can be transmitted from transplanted cells. 13,14 Finally, it is possible that some latent driver of both frailty and CLAD could explain our findings. If it turns out that 1 of the latter 2 broad potential relationships is true, it would suggest that frailty may be an early "biomarker" of CLAD risk rather than lying on the causal pathway.…”
Section: Discussionmentioning
confidence: 85%
“…For coculture experiments, primary human airway epithelial cells were seeded at 10,00 cells/well in sterile round-bottom 96-well plates and allowed to grow to 80%–90% confluence ( 61 ). Cells were exposed to hypoxia or normoxia for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Strategies to reduce such bias include adjusting for cell heterogeneity [68 ▪ ,77], purifying leukocyte subpopulations [58], or discarding any DNA-methylation differences potentially explained by changes in leukocyte composition [85,86]. Scarce studies used other samples and also found epigenetic abnormalities in muscle of adult critically ill patients [84 ▪ ], muscle stem cells of children after TBI [73 ▪ ], cerebrospinal fluid or surgically-resected brain biopsies of adult TBI patients [71 ▪ ,72], or airway epithelial cells from lung-transplant patients [70 ▪ ]. Second, due to the frequent urgency of ICU-admission, it is difficult to establish to what extent epigenetic abnormalities were already preexisting before ICU-admission or occurred de novo .…”
Section: The Epigenetic Legacy Of Critical Illness and Icu Feedingmentioning
confidence: 99%
“…Epigenetic research found its way to the field of critical illness only recently. Whereas initial studies focused on animal models, the last few years epigenetic abnormalities have also been documented in adult and pediatric patients with different types of critical illness, including sepsis [58–66], transplant and other major surgery [67,68 ▪ ,69,70 ▪ ], traumatic brain injury (TBI) or other major trauma [71 ▪ ,72,73 ▪ ,74], acute pancreatitis [75], and COVID-19 [76–79,80 ▪ ,81,82,83 ▪ ], as well as in heterogeneous cohorts [84 ▪ ,85–86]. Most studies focused on DNA-methylation [58–60,63–65,67,68 ▪ ,69,70 ▪ ,71 ▪ ,72,73 ▪ ,80 ▪ ,83 ▪ ,84 ▪ ,85–86], but also histone-modification/chromatin-accessibility [58,69,82] and noncoding RNAs [61,62,66,69,74,81] have been investigated.…”
Section: The Epigenetic Legacy Of Critical Illness and Icu Feedingmentioning
confidence: 99%